Status and prospects of Serbia’s accession to the world trade organization - Jelisavac-Trošić Sanja; Rapaić Stevan (Međunarodni Problemi)
For many years now Serbia is persistent in its attempt to become a full member of the World Trade Organization. Countries that are not yet members represent a tiny minority of the total world trade, and Serbia is one of them. Membership in the WTO is de facto requirement for accession to the European Union. This paper explains how far Serbia traveled in her way to this international organization, whose agreements are governing the global rules of trade between nations. Special attention was paid to the question why it is important that Serbia joins this organization, and what can be concluded from the accession experiences of countries in the region. The authors of this study will try to explain the importance of the WTO accession, and the manner in which membership in this organization will affect Serbia’s existing foreign trade relations. [Projekat Ministarstva nauke Republike Srbije, br. OI179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije u međunarodnim integrativnim procesima - spoljnopolitički, međunarodni, ekonomski, pravni i bezbednosni aspekti]